Pengaruh Literasi Keuangan dan Bandwagon Effect terhadap Perilaku Konsumtif Mahasiswa dengan Konsep Tri Nga - Putry, Nur Anita Chandra; Mutmainah, Mutmainah (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The study aims to analyze the influence of financial literacy and the bandwagon effect on students' consumptive behavior using the Tri Nga concept. Financial literacy plays a role in enhancing students' ability to manage finances, while the bandwagon effect often encourages impulsive consumptive behavior. The Tri Nga concept, consisting of Ngerti (understanding), Ngerasa (feeling), and Ngelakoni (doing), is used as an approach to examine students' consumptive behavior. The research method used is a quantitative approach with multiple linear regression analysis techniques. The sample consisted of 112 students in the Special Region of Yogyakarta. The results showed that financial literacy has a significant negative effect on the consumptive behavior of students with the Tri Nga concept, while the bandwagon effect has a significant positive effect on the consumptive behavior of students with the Tri Nga concept.